Formation of professional competence of students with active teaching methods - Kashuta, V. E.; Ryabovа, О. О. (Problems of Engineer-Pedagogical Education, 2018)
In the article theoretically grounded and developed a method of forming professional competence students of National University of Pharmacy on the subject "The first pre-medical аid" with active teaching methods means and make an assessment of its effectiveness. Much attention is paid to technique workshops. In order to enhance learning in the classroom applies solving situational tasks, practical skills to provide the first pre-medical aid, solving tests. We have developed a method of forming professional students' competence of active teaching methods has significantly increased cognitive activity of students and increased interest in the study of the discipline. During checking the effectiveness of the training methodology developed by us, it was revealed that the quality of the success of students' training was increased in comparison with the traditional teaching methods, which confirmed the effectiveness of the developed teaching methodology. The perspective is to further the implementation of active teaching methods in the teaching process.